Synchronous Ipsilateral High Submuscular Placement of Prosthetic Balloons and Reservoirs. Issue 2 (12th January 2017) - Kavoussi, Nicholas L.; Hofer, Matthias D.; Viers, Boyd R.; Cordon, Billy H.; Mooney, Ryan P.; Pagliara, Travis J.; Scott, Jeremy M.; Morey, Allen F.
Abstract: Introduction: Synchronous ipsilateral high submuscular placement of artificial urinary sphincter (AUS) pressure-regulating balloons (PRBs) and inflatable penile prosthesis (IPP) reservoirs in a single submuscular tunnel is a novel strategy that could be advantageous for patients who have had major pelvic surgery. Aim: To report our initial experience with synchronous ipsilateral vs bilateral placement of AUS PRBs and IPP reservoirs in men undergoing implant surgery. Methods: We retrospectively reviewed all patients undergoing synchronous AUS and IPP placement from 2007 through 2015 by a single surgeon at our tertiary center. Patients were stratified according to ipsilateral vs bilateral placement of the AUS PRB and IPP reservoir. Main Outcome Measures: Reoperation rates because of infectious or erosive complications and mechanical failure were assessed. Results: Of the 968 implant surgeries during the study period, 47 men had synchronous device placement, of whom 17 (36%) underwent ipsilateral placement of the PRB and reservoir. During a median follow-up of 19 months (range = 1–84 months), reoperations were necessary in 12 of 47 (26%) and were similar between groups (ipsilateral, 5 of 17, 29%; bilateral, 7 of 30, 23%; P = .73). Most reoperations were due to AUS-related complications (10 of 12, 83%) and nearly all patients with reoperation (10 of 12, 83%) had compromised urethras (ie, prior urethral surgery, radiation, or prior AUS implantation). The most common indication for reintervention was cuff erosion (4 of 47, 9%), with no difference between groups (ipsilateral, 3 of 17, 18%; bilateral, 1 of 30, 3%; P = .13). Conclusion: Synchronous ipsilateral high submuscular placement of urologic prosthetic balloons could safely facilitate prosthetic surgery in patients with a history of major pelvic and inguinal surgery.